State of the art review of the environmental assessment and risks of underground geo-energy resources exploitation. (September 2017) - Liu, Wen; Ramirez, Andrea
Abstract: Geo-resources play an increasing significant role in achieving a sustainable energy future. However, their exploitation is not free of environmental impacts. This paper aims to identify the lessons and knowledge gaps on understanding of the sources, mechanisms and scope of environmental consequences of underground geo-energy resources exploitation. The paper examines four underground exploitation activities: CO2 geological storage, exploitation of shale gas, geothermal power and compressed air energy storage (CAES). Selected studies carrying out life cycle assessment (LCA) and environmental risk assessment (ERA) are structurally reviewed by applying a six steps method. Our finding indicates that global warming potential is the major focus of examined LCA studies with relatively less attention on other impacts. Environmental impacts at the local level are less evaluated except water use for shale gas and geothermal power. Environmental impacts of exploitation with storage purposes are relatively low. For energy supply associated exploitation, the impacts largely depend on the types of underground activities and the exploited energy carriers. In the ERA studies, likelihood of a hazard occurrence is the focus of the probability assessment. There is limited information on the pathways and transport of hazard agents in the subsurface and on the relation between hazard exposure and the impacts. The leakage of the storing agents is the well-identified hazard for storage associated exploitation, while the migration of fluids and exploited energy carriers are the ones for exploitation with energy supply purposes. In general, understanding of environmental risks of soil contamination are limited. Very few number of ERA studies are available for assessing a CAES. Our research points out the need for developing a framework which allows the integration between LCA and ERA in subsurface environmental management.